A Contact Network-Based Approach for Online Planning of Containment Measures for COVID-19 - Thomaz, Guilherme; Mauá, Denis; Barros, Leliane (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2020: Anais do XVII Encontro Nacional de Inteligência Artificial e Computacional, 2020)
We use data from the 2017 Origin-Destination survey to build a representative contact network for the city of São Paulo, where individuals are connected by different social relations (school, work, neighborhood, household). The network is used to devise a discrete time and state compartmental model for the spread of the COVID-19. We employed the model to compare different mitigation strategies. The results show that even simple Monte Carlo planners greatly improve the performance over reactive strategies in terms of balancing the economical and the health impacts of non-pharmaceutical interventions.